PERNIKAHAN USIA DINI PADA MASYARAKAT MELAYU DIDESA BATU AMPAR KECAMATAN KEMUNING KABUPATEN INDRAGIRI HILIR - Anzalina, Freti; Jalil, Ashaluddin (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
Early marriage is underage marrieage when a person marries under the age of 21. Early marriage in the village of Batu Ampar, in ancient time only a few, and factors that cause only  economic factors. Parents are not able send their children to school, and chose to marry her off so as to reduce the family economy. But along with the development of the age that is the cause of early marriage in the village of batu ampar not only because of economic factor, but there are many factors behind the occurrence of early marriage. In the tradition of malay Batu Ampar stone there is a marriage that is prohibited because it is considered an adultery, the marriage is an eloperment, elopement marriage and nyerumahi. In the past, marriage was prohibited and there were sanctions if someone did it. But today the forbidden marriage is an excuse for children in the village of Batu Ampar as an excuse to get married at an early age, they do it so they can get married. The problem fotmulation in the research is 1. What marriage in the malay community in Batu ampar Village. 2. Whether the function of the family in an early marriage family functions. In this study using the theory of social change, whit the number of informants and subjects as many as 7 people consisting of the prince, the head of the malay customary institution and couples who engage in early marriage. The results of this study indicate that the occurrence of early marriage in the malay community in the village of  Batu Ampar consists of several factors, premarital pregnancy, economics and technological development. Keyword: Early Marriagee, Social Change, Malay Tradition